2018
DOI: 10.2174/1570161115666170821154841
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Latent Magnesium Deficiency in Obesity Decreases Positive Effects of Vitamin D on Cardiometabolic Risk Indicators

Abstract: CLMD and vitamin D deficiency may commonly be present in obese non-diabetic subjects. Individually and combined, both deficiencies predispose non-diabetic patients to increased risk of cardiometabolic diseases. Maintaining normal Mg status may improve the beneficial effects of vitamin D on cardiometabolic risk indicators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Prospective data on the effect of vitamin D supplementation in these patients will be collected and analyzed. Consistent evidences from large, randomized, placebo-control trials with adequate statistic power and eventually exploring the association of vitamin D and other nutritional elements ( 46 ) are warranted to confirm these findings.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Prospective data on the effect of vitamin D supplementation in these patients will be collected and analyzed. Consistent evidences from large, randomized, placebo-control trials with adequate statistic power and eventually exploring the association of vitamin D and other nutritional elements ( 46 ) are warranted to confirm these findings.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, the concomitant deficiency of magnesium and vitamin D in obesity has been associated with an increased risk of cardiometabolic disease ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, chronic latent Mg 2+ deficiency and/or Vitamin D deficiency predispose non-diabetic obese subjects to an increased risk of cardiometabolic diseases. Meanwhile, maintaining a normal Mg 2+ status improves the beneficial effect of Vitamin D on cardiometabolic risk indicators [ 57 ]. Interestingly, an interventional study performed on healthy women showed a significant increase in serum concentration of Mg 2+ in obese but not in non-obese subjects after vitamin D intramuscular injection, probably caused by increased Mg 2+ renal retention induced by vitamin D and emphasized by baseline Mg 2+ deficiency of the obese subjects [ 58 ].…”
Section: Mg 2+ and Obesitymentioning
confidence: 99%
“…Absorption and excretion is under hormonal control. However, there is no one single hormon responsible for Mg homeostasis but parathyroid hormone, estrogen, calcitonin, glucagon and 1,25-dihydroxyvitamin D surely influence together the balance of intake, utilization and excretion [9,10].…”
Section: Magnesium the Indispensible Cationmentioning
confidence: 99%